Coenzyme Q10 Biosynthesis Established in the Non-Ubiquinone Containing Corynebacterium glutamicum by Metabolic Engineering - Burgardt, Arthur; Moustafa, Ayham; Persicke, Marcus; Sproß, Jens; Patschkowski, Thomas; Risse, Joe Max; Peters-Wendisch, Petra; Lee, Jin-Ho; Wendisch, Volker F. (Frontiers in Bioengineering and Biotechnology, 2021)
Coenzyme Q10 (CoQ10) serves as an electron carrier in aerobic respiration and has become an interesting target for biotechnological production due to its antioxidative effect and benefits in supplementation to patients with various diseases. For the microbial production, so far only bacteria have been used that naturally synthesize CoQ10 or a related CoQ species. Since the whole pathway involves many enzymatic steps and has not been fully elucidated yet, the set of genes required for transfer of CoQ10 synthesis to a bacterium not naturally synthesizing CoQ species remained unknown. Here, we established CoQ10 biosynthesis in the non-ubiquinone-containing Gram-positive Corynebacterium glutamicum by metabolic engineering. CoQ10 biosynthesis involves prenylation and, thus, requires farnesyl diphosphate as precursor. A carotenoid-deficient strain was engineered to synthesize an increased supply of the precursor molecule farnesyl diphosphate. Increased farnesyl diphosphate supply was demonstrated indirectly by increased conversion to amorpha-4,11-diene. To provide the first CoQ10 precursor decaprenyl diphosphate (DPP) from farnesyl diphosphate, DPP synthase gene ddsA from Paracoccus denitrificans was expressed. Improved supply of the second CoQ10 precursor, para-hydroxybenzoate (pHBA), resulted from metabolic engineering of the shikimate pathway. Prenylation of pHBA with DPP and subsequent decarboxylation, hydroxylation, and methylation reactions to yield CoQ10 was achieved by expression of ubi genes from Escherichia coli. CoQ10 biosynthesis was demonstrated in shake-flask cultivation and verified by liquid chromatography mass spectrometry analysis. To the best of our knowledge, this is the first report of CoQ10 production in a non-ubiquinone-containing bacterium.